The Hunger Strike versus the role of the State as guarantor of the fundamental Human Rights of the citizen (Legal journal - Research in Legal and Social Sciences, 2017)
The purpose of this investigation is to analyze an extreme conduct, with special characteristics and a broad legal scope, which poses an important media scenario, as well as being delicate for public authorities. The hunger strike implies, for those who take the initiative to undertake it, the risk of highly personal interests that affect fundamental rights recognized and guaranteed by the constitution. It is intended to examine this phenomenon in an integral way to guarantee an approach in the most complete way possible. Therefore, the material is divided into two parts that are detailed below. In the first, an exhaustive analysis is made of the main fundamental rights that the protester voluntarily decides to put to the test, such as: life, physical integrity and health. Its concepts, characteristics and legal protection at national and international level are detailed. In the second, the relationship of these innate rights to all is detailed, with the position assumed by the person who initiates the hunger strike process. Finally, it enters the study of the hunger strike in particular, with all its edges and characteristics; all with the aim of reaching a conclusion that offers recommendations on the multidisciplinary and legal technical measures to be taken around the affected party in order to seek the cessation of the measure, considering with the interventions the absolute respect for their freedom of expression and dignity. human.